Pediculosis Capitis dan Personal Hygiene pada Anak SD di Daerah Pedesaan Kotamadya Banjarbaru - Rifqoh Mukhtar Mayasin; Wahdah Norsiah (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2017)
Pediculosis capitis or head lice infestation caused by Pediculus humanus var. capitis. Its caused irritation and scalp pruritus. Its occurs most commonly in children becaused they couldn’t keep their personal hygiene independently. Pediculosis capitis caused disconcentrated, lack of sleep, parental anxiety, social embarrassment and isolation. The objective of this study was to determine the correlation between Pediculosis capitis with personal hygiene in rural primary schoolchildren in Cempaka Village, Banjarbaru Municipality. This analytic observational case control study design, at first determined 33 (19,87%) schoolchildren was infested pediculosis capitis from 166 population. Other 33 schoolchildren randomized uninfested pediculosis capitis as the controls group (1:1 to case group). Pediculosis capitis was known by identified head lice, nymph or eggs of Pediculus humanus var. capitis and personal hygiene was measured by questionnaire. Chi Square test result, there was significant moderate positive correlation between pediculosis capitis with personal hygiene (p value